-4+9=13x-2-12x

Simple and best practice solution for -4+9=13x-2-12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+9=13x-2-12x equation:


Simplifying
-4 + 9 = 13x + -2 + -12x

Combine like terms: -4 + 9 = 5
5 = 13x + -2 + -12x

Reorder the terms:
5 = -2 + 13x + -12x

Combine like terms: 13x + -12x = 1x
5 = -2 + 1x

Solving
5 = -2 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5 + -1x = -2 + 1x + -1x

Combine like terms: 1x + -1x = 0
5 + -1x = -2 + 0
5 + -1x = -2

Add '-5' to each side of the equation.
5 + -5 + -1x = -2 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = -2 + -5
-1x = -2 + -5

Combine like terms: -2 + -5 = -7
-1x = -7

Divide each side by '-1'.
x = 7

Simplifying
x = 7

See similar equations:

| 3x+86=8x-9 | | 14+6a-8=28 | | -4x^2+10x+6=0 | | (x+7)(x-7)=32 | | 8x-11=-3x-4 | | 5(X-1)=10-2(3X+2) | | 3x^2-12x(1.5)= | | 5+.5c=14 | | 2(x-5)-x=-6 | | 72-5x=13x+20 | | 6+5n=9-2n | | 0.07x*0.03=0.38 | | 1.4(a+6)=2.8(a+10) | | -97-8x=60-22x | | 112=1.5s | | 6x(2x+7)= | | 9+3(-7y+1)=6(y+7)+6 | | 50+65+x=505 | | 4x-3=7x+18 | | 6x(2x-7)= | | 9x=14x-21 | | -7x+11=19-x | | 3+10n=12n-3 | | 0-5x=6x+19 | | (y/4)=-10 | | g(x)=x^2-2X+5 | | x^3+3sinx+2cosx=2 | | 85-6x=w | | 2-5y=18 | | 3x-7+4=28 | | 2432+42= | | 5x+2+4x=7+2x-4 |

Equations solver categories